Clinical impact of exercise in patients with peripheral arterial disease. (August 2017) - Novakovic, Marko; Jug, Borut; Lenasi, Helena
Increasing prevalence, high morbidity and mortality, and decreased health-related quality of life are hallmarks of peripheral arterial disease. About one-third of peripheral arterial disease patients have intermittent claudication with deleterious effects on everyday activities, such as walking. Exercise training improves peripheral arterial disease symptoms and is recommended as first line therapy for peripheral arterial disease. This review examines the effects of exercise training beyond improvements in walking distance, namely on vascular function, parameters of inflammation, activated hemostasis and oxidative stress, and quality of life. Exercise training not only increases walking distance and physiologic parameters in patients with peripheral arterial disease, but also improves the cardiovascular risk profile by helping patients achieve better control of hypertension, hyperglycemia, obesity and dyslipidemia, thus further reducing cardiovascular risk and the prevalence of coexistent atherosclerotic diseases. American guidelines suggest supervised exercise training, performed for a minimum of 30–45 min, at least three times per week, for at least 12 weeks. Walking is the most studied exercise modality and its efficacy in improving cardiovascular parameters in patients with peripheral arterial disease has been extensively proven. As studies have shown that supervised exercise training improves walking performance, cardiovascular parameters and quality of life in patients with peripheral arterial disease, it should be encouraged and more often prescribed.